(untitled) (Cadernos de Letras da UFF, 2020)
My research examines the staging contexts of these case studies, locating them among the traumatic histories they were drawn from, which centre on women saying, sometimes loudly, and sometimes quietly, #MeToo. However, they said this traditionally in isolated historical contexts, dominated by the overwhelming power of the Irish institutions of church, family, and nation, and without the immediate collective community that one can access online today. For the women depicted in these productions, there was little opportunity to challenge the normalised patterns of abuse they were subjected to as part of conservative ideologies regarding gender, the family, and religion that were inextricably linked to the strong relationship between church and state in twentieth century Ireland.